Economic Alchemy: Unraveling the Nexus between Trade Openness, Inflation, Exchange Rates, and Economic Growth in Bangladesh - Ridwan, Mohammad; Tahsin, Muhtasib Sarker; Al-Absy, Mujeeb Saif Mohsen; Eleais, Md.; Ridzuan, Abdul Rahim; Mukthar, K.P. Jaheer (International Journal of Economics and Financial Issues, 2025)
This empirical research explores the impacts and causality relationship between Bangladesh’s trade openness, exchange rate, inflation, population, and economic development using yearly time series data from 1990 to 2020. Inflation, exchange rate, and population were also included as explanatory variables in this research. Throughout this time frame (1990-2020), Bangladesh implemented various trade liberalization policies to grow trade and stimulate the economy. This research used the ARDL bound test and found that economic growth is cointegrated with independent variables. This study also utilized DOLS to observe the long-run relationship. FMOLS and CCR estimators were used to check robustness. The Granger Causality test was used to demonstrate unidirectional causality between trade openness and economic growth, while the Augmented Dickey-Fuller unit root test, Philips-Perron, and IPS unit root test were used to detect stationary. The outcome of this model exhibits that, except for population, all independent variables have a significant long-run relationship with economic growth. Trade openness has a negative association with economic growth and is significant. Meanwhile, inflation, exchange rate, and population have a positive relation with economic growth. The impact of inflation and population coefficients is significant. The robustness results are matched with the baseline DOLS model. This empirical study demonstrated that all variables are stationary, with or without a trend, and a unidirectional causal relationship was detected between trade openness and economic growth, with trade openness boosting economic growth. To boost Bangladesh’s economic development, policymakers should prioritize export promotion strategies. To ensure a high level of national output, it is necessary to maximize the utilization of capital goods and decrease reliance on noncapital items. The volatility of exchange rates and the inflation rate must be incorporated to foster economic growth.